Immobilization of lipase from Candida Rugosa on chitosan beads for transesterification reaction. - Hasrul Azmi, Said (2008)
The objective of this study was to evaluate the immobilization of lipase on a chitosan support by physical adsorption, aiming its application in transesterification reactions. Immobilization of lipase give several advantages such as improved stability, reuse, continuous operation and the possibility of better control of reactions. Chitosan offers several advantages as an enzyme immobilization carrier such as versatility of available physical forms (flakes, porous beads, gel, fiber and membrane), low biodegradability and easy handling. In this study, bead porous of chitosan was used for immobilizing lipase from a microbial source of Candida rugosa. Lipase was immobilized by physical adsorption on chitosan following a previously developed methodology by Carneiro da Chunca et al. (1999). The ability of immobilized lipase on chitosan beads to catalyze transesterification of cooking oil and methanol was investigated. The important parameters like reaction time and oil to methanol molar ratios were studied to indentify the comparison between free lipase and immobilized lipase on transesterification reaction. From the study it was found that maximum conversion of ester using immobilized lipase and free lipase were 72.25% and 76.5% obtained at the optimum conditions of 1:4 molar ratios and reaction time of 48 hour. Therefore, the conversion of ester for free lipase was higher than immobilized lipase. As a conclusion, the chitosan beads were appear as a suitable support for immobilized lipase on trasnesterification reaction even though the ester conversion was lower than free lipase. On the other hand, immobilized lipase was provided an important advantage such as easy separation from the product and has a high potential to reuse.